Colon Rectal Liver Metastases: The Role of the Liver Transplantation in the Era of the Transplant Oncology and Precision Medicine - Finotti, Michele; Vitale, Alessandro; Gringeri, Enrico; D'Amico, Francesco Enrico; Boetto, Riccardo; Bertacco, Alessandra; Lonardi, Sara; Bergamo, Francesca; Feltracco, Paolo; Cillo, Umberto (Frontiers in Surgery, 2021)
The development of liver metastases in colon rectal cancer has a strong impact on the overall survival (OS) of the patient, with a 5-year survival rate of 5% with palliative treatment. Surgical resection combined with pharmacological treatment can achieve a 5-year OS rate of 31–58%. However, in only 20% of patients with colon rectal liver metastases (CRLMs), liver resection is feasible. In highly selected patients, recent trials and studies proved that liver transplantation (LT) for non-resectable CRLM is a surgical option with an excellent long-term OS. The paper aims to review the indications and outcome of LT for CRLMs, with a special focus on immunosuppressive therapy and the management of local and extrahepatic recurrence after LT.